A Study On The Demographic Factors Influencing The Consumers Buying Behaviour With Special Reference To The Organic Food Product Brands In Bangalore City (International Journal of Food and Nutritional Sciences, 2022)
This study explores the demographic factors influencing consumer buying behavior regarding organic food product brands in Bangalore City. Utilizing a sample of 466 respondents, the research investigates how variables such as age, education, income, and gender impact preferences and purchasing decisions in the organic food market. The findings indicate that younger consumers (ages 21-30) exhibit a strong preference for brands like Dear Earth and Dhatu, while middle-aged consumers (ages 31-40) favor Down to Earth. Additionally, higher education levels correlate with a preference for 24 Mantra, reflecting increased awareness of health and wellness benefits associated with organic products. Income analysis reveals that budget-conscious consumers under ₹10,000 gravitate towards affordable brands, while those earning between ₹10,000 and ₹30,000 consistently prefer 24 Mantra. Overall, the study highlights the significance of demographic factors in shaping consumer behavior and provides valuable insights for marketers in the organic food sector.